2020
DOI: 10.18632/oncotarget.27493
|View full text |Cite
|
Sign up to set email alerts
|

DOT1L inhibition is lethal for multiple myeloma due to perturbation of the endoplasmic reticulum stress pathway

Abstract: The histone 3 lysine 79 (H3K79) methyltransferase (HMT) DOT1L is known to play a critical role for growth and survival of MLL-rearranged leukemia. Serendipitous observations during high-throughput drug screens indicated that the use of DOT1L inhibitors might be expandable to multiple myeloma (MM). Through pharmacologic and genetic experiments, we could validate that DOT1L is essential for growth and viability of a subset of MM cell lines, in line with a recent report from another team. In vivo activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…This dichotomy, among other factors, likely contributes to the failure to adopt an identity of terminally differentiated plasma cells. Plasma cells strongly depend on the endoplasmic reticulum (ER) stress pathway (Gass et al , 2004), and recently, DOT1L has been connected to the expression of unfolded protein response (UPR) genes involved in this pathway (Dafflon et al , 2020). However, our data from activated B cells revealed that the expression of most UPR genes remained unchanged in the absence of DOT1L.…”
Section: Resultsmentioning
confidence: 99%
“…This dichotomy, among other factors, likely contributes to the failure to adopt an identity of terminally differentiated plasma cells. Plasma cells strongly depend on the endoplasmic reticulum (ER) stress pathway (Gass et al , 2004), and recently, DOT1L has been connected to the expression of unfolded protein response (UPR) genes involved in this pathway (Dafflon et al , 2020). However, our data from activated B cells revealed that the expression of most UPR genes remained unchanged in the absence of DOT1L.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, methylation of histone H3 lysine 4 (H3K4), histone H3 lysine 36 (H3K36), and histone H3 lysine 79 (H3K79) is generally associated with transcriptional activation, while methylation of histone H3 lysine 9 (H3K9), histone H3 lysine 27 (H3K27) and histone H4 lysine 20 (H4K20) is associated with gene silencing 6 . Dysregulation of histone methylation is deeply involved in the pathogenesis of MM, and recent preclinical studies have demonstrated the antimyeloma effects of inhibitors of EZH2, a H3K27 methyltransferase 7 9 , and DOT1L, a H3K79 methyltransferase 10 , 11 . Indeed, as a result of its promising efficacy against MM, patients with relapsed or refractory MM were recently recruited for a phase I clinical trial of the EZH2 inhibitor, GSK126 (also known as GSK2816126) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The reduced expression of the H3K4 demethylase KDM1A due to a germline mutation in MGUS and MM was shown to drive proliferation via MYC activation. Interestingly, transcriptomes from patients with KDM1A mutations showed enrichment in the pathways associated with both intrinsic MM pathogenesis and MM-BMME interactions in comparison with KDM1A wild-type patients, again suggesting the importance of epigenetic modifications in the interaction between MM plasma cells and the BMME [88].…”
Section: Lysine Demethylases (Kdms) In MMmentioning
confidence: 95%